Sanatorium, Health and Recreation Facilities and Their Volume, Spatial, Planning Solutions (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Sanatoriums, sanatoriums and recreation facilities are facilities designed for health restoration, strengthening, relaxation and prevention of various diseases. They provide healing and recreational services using natural resources. Such institutions play an important role in improving the health of the population and improving their quality of life. Volumetric, spatial and planning solutions of health and recreation facilities are developed in accordance with their functional goals, location area and user needs. These facilities must not only provide treatment and recreation, but also embrace comfort, aesthetic beauty, and environmental sustainability.